2019
DOI: 10.1016/j.conbuildmat.2019.116828
|View full text |Cite
|
Sign up to set email alerts
|

Biocementation of sand by Sporosarcina pasteurii strain and technical-grade cementation reagents through surface percolation treatment method

Abstract: Biocementation of sand by Sporosarcina pasteurii strain and technical-grade cementation reagents through surface percolation treatment method

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(54 citation statements)
references
References 56 publications
(102 reference statements)
9
45
0
Order By: Relevance
“…In general, their results have indicated that the rate of urea hydrolysis increases with increasing temperature, suggesting that the urease of most of the soil bacteria is not heat inactivated (up to the temperature ranging 45-60 °C). For an example, urease activity of Sporosarcina Pasteurii increased proportionally with temperature between 25 °C and 60 °C [24]. The similar tendency is reported for Pararhodobacter sp.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In general, their results have indicated that the rate of urea hydrolysis increases with increasing temperature, suggesting that the urease of most of the soil bacteria is not heat inactivated (up to the temperature ranging 45-60 °C). For an example, urease activity of Sporosarcina Pasteurii increased proportionally with temperature between 25 °C and 60 °C [24]. The similar tendency is reported for Pararhodobacter sp.…”
Section: Discussionsupporting
confidence: 78%
“…The enzymes of the bacteria are thermal sensitive and can readily be denatured by even a slight change of environmental temperature [22]. Most of the MICP studies have employed Sporosarcina pasteurrii for urea hydrolysis due to the highly active urease enzyme [5,6,11,13,[23][24][25]. Only a few MICP studies focused on introducing some other ureolytic strains including Bacillus sphaercus (MCP-11) [26], Pararhodobactor sp.…”
Section: Introductionmentioning
confidence: 99%
“…It can be observed that the calcite clusters that crystallized at particle contacts could enable the connectivity between soil particles, contributing as the primary source for strength and stability. Similar morphology of the calcium carbonate mineral could also be witnessed in other MICP-related works (Zhang et al 2017;Omoregie et al 2019). Moreover, there are crystals which were formed randomly on soil surfaces without subsidizing interparticle connection; by reducing the void spaces, however, those could secondarily contribute to the strength of the matrix (DeJong et al 2010).…”
Section: Effect Of Cementation Level On Durabilitysupporting
confidence: 73%
“…Food or technical grade chemicals have successfully been tested for S. pasteurii cultivation. Their application would additionally reduce costs 21 , 42 . For large scale industrial applications, media preparation and sterilization must also be considered for cost calculations 20 .…”
Section: Resultsmentioning
confidence: 99%